AN ANALYSIS OF STUDENTS’ LEARNING READINESS TOWARDS HYBRID LEARNING ACHIEVEMENT IN ENGLISH - Hairis Shidiq Ghozali; Wiyaka; Siti Musarokah; Yoyok Andriyanto (STKIP Subang, 2023)
ABSTRACT This study used a descriptive qualitative approach to analyze students' readiness for hybrid learning achievement in English. Data were collected through questionnaires and interviews. The study aimed to (1) assess the extent to which students of SMK N 7 Semarang were ready to adopt the hybrid learning model in English learning, (2) identify the factors that hindered the readiness of students of SMK N 7 Semarang in implementing the hybrid learning model in English learning, and (3) identify the factors that supported the readiness of students of SMK N 7 Semarang in implementing the hybrid learning model in English learning. The subjects of the study were students of class XI TFLM 1 SMK N 7 Semarang. The results of the study showed that (1) students of SMK N 7 Semarang had adequate readiness to adopt hybrid learning in English learning, with a readiness level of 65.57%, (2) factors that hindered students' readiness involved facility constraints, skills, and motivation in online learning, and (3) factors that supported students' readiness included guidance from teachers, support from parents, and cooperation among students. The study concluded that hybrid learning had the potential to improve the quality of English learning if students had a high level of learning readiness. Therefore, the recommendations from this study were that teachers and schools should provide adequate facilities, training, and encouragement to prepare students for hybrid learning. Keywords: Hybrid learning, Learning readiness, Learning achievement